2017
DOI: 10.1044/2017_aja-16-0123
|View full text |Cite
|
Sign up to set email alerts
|

International Outcome Inventory for Hearing Aids: Data From a Large Swedish Quality Register Database

Abstract: o r P e e r R e v i e w Abstract Purpose: The purpose of this study was to analyze a data-base of completed IOI-HA questionnaires obtained from over 100 000 clients fitted with new hearing aids in Sweden during the period 2012-2016. Mean IOI-HA total scores were correlated with degree of hearing loss, unilateral vs bilateral fitting, first-time vs return clients, gender, and variation among dispensing clinics. The correlations with expectations, service quality and technical functioning of the hearing aids wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
3
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 17 publications
6
26
3
1
Order By: Relevance
“…48,49 Several studies have found that success and satisfaction with hearing aids were correlated with the perceived care from and satisfaction with their HCP during the fitting and counseling process. [50][51][52][53] These results indicate that, for those who have received HCP-fit hearing aids, the HCP plays an important role in getting the user to be successful and satisfied with their hearing aids. Lack of access to an HCP may affect success and satisfaction with OTC hearing aids, consistent with findings that those dissatisfied with self-fit hearing aids became more satisfied and successful with subsequent help from an HCP.…”
Section: Over-the-counter Challengesmentioning
confidence: 99%
“…48,49 Several studies have found that success and satisfaction with hearing aids were correlated with the perceived care from and satisfaction with their HCP during the fitting and counseling process. [50][51][52][53] These results indicate that, for those who have received HCP-fit hearing aids, the HCP plays an important role in getting the user to be successful and satisfied with their hearing aids. Lack of access to an HCP may affect success and satisfaction with OTC hearing aids, consistent with findings that those dissatisfied with self-fit hearing aids became more satisfied and successful with subsequent help from an HCP.…”
Section: Over-the-counter Challengesmentioning
confidence: 99%
“…Also, according to this research, there is a difference between men and women in some items. In other words, women have earned higher points in the "impact on others" item in the IOI-HA questionnaire [52].…”
Section: Hearing Aid Featuresmentioning
confidence: 99%
“…The amount of hearing loss experienced by a person has a positive correlation with the amount of hearing aids use, and there is a correlation between the person's report of the hearing problem and the rate of hearing aids use. However, the lack of relationship between hearing loss (pure-tone-average) and satisfaction and hearing aids has also been reported, suggesting that hearing loss alone may not be a good predictor of the usefulness of hearing aids [51,52].…”
Section: Patient's Auditory Performancementioning
confidence: 99%
“…The audiogram defines the thresholds at which a sine wave tone can be perceived, in order to determine which frequencies should be amplified to compensate for the hearing loss. A mild hearing loss may involve a 20-40 dB decline across frequency bands, typically spanning from mid range (2-4 kHz) to high range (5)(6)(7)(8)(9)(10). However, this test measures only the sensitivity to an artificially produced tone, rather than the sounds that characterize a normal listening experience.…”
Section: The Lack Of Personalization In Hearing Health Carementioning
confidence: 99%
“…Studies analyzing outcome measures capturing the user satisfaction indicate that this is largely determined by two factors: (1) whether the user perceives an improved quality of life through use of the devices, and (2) to what degree they help overcome limitations when interacting with others around the user. The degree to which the user feels involved in the traditional clinical fitting process highly impacts the overall satisfaction [10]. Alternative models for selling hearing aids over the counter based on do-it-yourself audiometry tests may technically provide the same fitting as provided in a clinical setting [11].…”
mentioning
confidence: 99%